2022
DOI: 10.3390/su142416661
|View full text |Cite
|
Sign up to set email alerts
|

Use of E-Waste in Metakaolin Blended Cement Concrete for Sustainable Construction

Abstract: This paper investigates the use of non-metallic portion (NMP) reclaimed from e-waste (i.e., waste printed circuit board—PCB) as replacement of natural sand in the blended cement concrete by using Metakaolin (MK) as supplementary cementitious material for its effect on the mechanical, durability, microstructural, and mineralogical properties of concrete. It was found that the blended mixes containing NMP and MK outperformed the control mix. With the addition of 10% NMP and 10% MK, the maximum compressive streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…And the water absorption of concrete decreased by 9.7%, and for mortar it decreased by 9.3%. This is in good agreement with the works of a number of authors, in particular with the works [13][14][15][16][17][18][19] devoted to the processes of structure formation of concrete composites using coal dust and the works of the authors [20][21][22][23][24][25][26][27] devoted to the physical and mechanical characteristics of concrete modified with coal dust. Based on the results of XRD analysis of concrete of the control composition, the phases of portlandite, illite, anorite, calcite and quartz were identified.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…And the water absorption of concrete decreased by 9.7%, and for mortar it decreased by 9.3%. This is in good agreement with the works of a number of authors, in particular with the works [13][14][15][16][17][18][19] devoted to the processes of structure formation of concrete composites using coal dust and the works of the authors [20][21][22][23][24][25][26][27] devoted to the physical and mechanical characteristics of concrete modified with coal dust. Based on the results of XRD analysis of concrete of the control composition, the phases of portlandite, illite, anorite, calcite and quartz were identified.…”
Section: Resultssupporting
confidence: 90%
“…It should be noted that, based on the results of the literature review, no studies were found on the use of coal dust with a similar chemical composition as a partial replacement for binders in the technology of cement composites. However, there are a number of studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] where the use of inert mineral additives, namely, clay, metakaolin, electric arc furnace dust, stone dust and finely ground sea shell powders, as a partial replacement for cement allows in rational amounts the improvement of the physical and mechanical characteristics of the composite and at the same time an increase in its environmental friendliness. The optimal percentages for replacing part of the cement with these types of additives varied from 2% to 20%, while improvements in the strength characteristics, water absorption and porosity of experimental cement composites were observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations